2022
DOI: 10.5194/acp-22-12287-2022
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of secondary ice production on microphysics and dynamics in tropical convection

Abstract: Abstract. Secondary ice production (SIP) is an important physical phenomenon that results in an increase in the ice particle concentration and can therefore have a significant impact on the evolution of clouds. In this study, idealized simulations of a mesoscale convective system (MCS) were conducted using a high-resolution (250 m horizontal grid spacing) mesoscale model and a detailed bulk microphysics scheme in order to examine the impacts of SIP on the microphysics and dynamics of a simulated tropical MCS. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 89 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…Ice particles produced by rime splintering increased collection of supercooled rain and led to an increase of snow and ice pellet accumulation in regions where FR was incorrectly predicted by the model without HM . In addition to the influence of SIP on microphysical properties in deep convection as shown in past studies (e.g., Qu et al., 2022), our results indicate the importance of SIP in correctly simulating precipitation type for winter storms. Our results also suggest the potential for using the predicted hydrometeor properties to forecast winter precipitation types explicitly.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Ice particles produced by rime splintering increased collection of supercooled rain and led to an increase of snow and ice pellet accumulation in regions where FR was incorrectly predicted by the model without HM . In addition to the influence of SIP on microphysical properties in deep convection as shown in past studies (e.g., Qu et al., 2022), our results indicate the importance of SIP in correctly simulating precipitation type for winter storms. Our results also suggest the potential for using the predicted hydrometeor properties to forecast winter precipitation types explicitly.…”
Section: Discussionsupporting
confidence: 85%
“…However, many of these remain poorly quantified. Recent modeling studies have demonstrated the importance of SIP for convective cases, where SIP leads to increased ice concentrations and mass contents aloft (e.g., Hou et al., 2023; Hua et al., 2023; Huang et al., 2021; Qu et al., 2022) and accelerated cloud glaciation (e.g., Connolly et al., 2006; Lawson et al., 2015; Miltenberger et al., 2020; Phillips et al., 2005; Sullivan et al., 2017). However, there have been fewer studies of SIP impacts on stratiform clouds or in winter storm cases, and, to our knowledge, no studies examining the impacts of SIP on FR.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the successful simplifications could mean that these processes are unimportant in the atmosphere. However, both are usually believed to be important processes for ICNC (Kanji et al., 2017; Kärcher et al., 2022; Korolev & Leisner, 2020; Qu et al., 2022; Villanueva et al., 2021) and thus the model behavior seems faulty. The insensitivity of ECHAM‐HAM to heterogeneous freezing (formulations) has been documented before (Dietlicher, 2018; Dietlicher et al., 2019; Hoose, Lohmann, Erdin, & Tegen, 2008; Ickes et al., 2022; Villanueva et al., 2021) but never as clearly as in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…It is significant to explore how the characteristics of the cloud condensation nuclei over such a mountainous coastal region influence those microphysical processes and the formation of heavy rainfall. Last but not least, uncertainties of ice‐phase processes and their roles in storm dynamics and precipitation (Morrison et al ., 2020; Huang et al ., 2021, 2022; Qu et al ., 2022) need to be examined as well.…”
Section: Discussionmentioning
confidence: 99%